The xerobranching response represses lateral root formation when roots are not in contact with water - Orman-Ligeza, Beata; Morris, Emily C.; Parizot, Boris; Lavigne, Tristan; Babé, Aurelie; Ligeza, Aleksander; Klein, Stephanie; Sturrock, Craig; Xuan, Wei; Novák, Ondřey; Ljung, Karin; Fernandez, Maria; et al. (Elsevier (Cell Press), 2018)
Efficient soil exploration by roots represents an important target for crop improvement and food security [1, 2]. Lateral root (LR) formation is a key trait for optimising soil foraging for crucial resources such as water and nutrients. Here, we report an adaptive response termed xerobranching, exhibited by cereal roots, that represses branching when root tips are not in contact with wet soil. Non-invasive X-ray microCT imaging revealed that cereal roots rapidly repress LR formation as they enter an air space within a soil profile and are no longer in contact with water. Transcript profiling of cereal root tips revealed that transient water deficit triggers the abscisic acid (ABA) response pathway. In agreement with this, exogenous ABA treatment can mimic repression of LR formation under transient water deficit. Genetic analysis in Arabidopsis revealed that ABA repression of LR formation requires the PYR/PYL/RCAR-dependent signalling pathway. Our findings suggest that ABA acts as the key signal regulating xerobranching. We conclude that this new ABA-dependent adaptive mechanism allows roots to rapidly respond to changes in water availability in their local micro-environment and to use internal resources efficiently.